2022
DOI: 10.1177/00405175221086046
|View full text |Cite
|
Sign up to set email alerts
|

A study on the dynamic motion of floating fibers in the double apron drafting process

Abstract: Double apron drafting is an important unit in yarn spinning; the motion of fibers during the double apron drafting zone directly determines the quality of the final yarn. In this research, we sought to study how the motion of the fibers and the irregularities introduced during the double apron drafting process were affected by the processing settings and fiber properties. The fiber acceleration point under different drafting conditions was investigated using the tracer fiber technique. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The unevenness of the yarn is typically recognized to be linked to fiber movement. 21,27 The drafting device’s operation and the distribution of friction forces in the main drafting zone have a significant impact on controlling the accelerations of floating fibers. As previously mentioned, the pressure distribution of the NDS features more and higher peaks than that of the DAD, which improves fiber movement control and reduces the number of floating fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The unevenness of the yarn is typically recognized to be linked to fiber movement. 21,27 The drafting device’s operation and the distribution of friction forces in the main drafting zone have a significant impact on controlling the accelerations of floating fibers. As previously mentioned, the pressure distribution of the NDS features more and higher peaks than that of the DAD, which improves fiber movement control and reduces the number of floating fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the two-velocity hypothesis, some other researchers tested the FAP distribution in a different drafting system with the method of the tracer fiber technique. [10][11][12][13][14][15] They are trying to build the relationship between the unstable movement of floating fibers and drafting parameters, and thus provide a basis for further research. It was found that the FAP distribution in simple roller drafting is more dispersed over a longer range, while the FAP distributions in the double apron drafting zone and the drafting zone with pressure bar are more concentrated and closer to front roller nip line.…”
mentioning
confidence: 99%